Tinjauan Kelengkapan Pengisian Discharge Summary Berdasarkan Regulasi SNARS (Standar Nasional Akreditasi Rumah Sakit) Edisi 1.1 di RSU Haji Medan - Erlindai Erlindai (Cybernetics: Journal Educational Research and Social Studies, 2021)
The completeness of filling out the discharge summary is very important for continuity of service, claims for BPJS and insurance, as well as being an assessment when hospital accreditation will be carried out listed in SNARS Edition 1.1 in the MIRM 15 standard subgroup. This study aims to determine the completeness of filling out a discharge summary based on SNARS regulations edition 1.1 at General Hospital of Haji Medan. The type of research used in this research is descriptive quantitative, with a population of 599 inpatient discharge summary forms at General Hospital of Haji Medan in July 2021 and a sample of 86 discharge summary forms. Based on the results of the study, it was found that the completeness of filling out the discharge summary was 29 forms of discharge summary (33,72%) and 57 forms of discharge summary were not filled out completely (66,28%). Based on the regulation of SNARS Edition 1.1 the score obtained for the total discharge summary is 33,72%, which is a score of 5 (partially fulfilled) because the achievement range is 20%-79%. The highest percentage of completeness in filling out the discharge summary based on SNARS Regulation Edition 1.1 at General Hospital of Haji Medan is status present, which is 80,23% and the lowest completeness is found in the components of important physical findings and other findings, which is 47,67 %. Suggestions that the author can give to the General Hospital of Haji Medan are it is better if the patient/ family signature component is added to the discharge summary form, there is a need to increase the discipline of doctors in filling out the discharge summary by conducting socialization about the importance of completing the discharge summary, spurring the motivation of doctors in filling out the discharge summary for example with a system of giving rewards and punishments and monitoring and evaluation needs to be done on the completeness of filling out the discharge summary in order to meet the subgroup of MIRM 15 standards in SNARS Edition 1.1.